2016
DOI: 10.1016/j.apjtm.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antiproliferative, antioxidant and antibacterial activities of essential oils from aromatic plants growing in Sudan

Abstract: The results suggest that the essential oils of these plants could be used as a source of natural anti-proliferative, antioxidant and antibacterial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 34 publications
2
17
1
3
Order By: Relevance
“…Although both oils showed different chemical profiles they exhibited high and comparable antiproliferative activity against the three tested cancer cell lines with IC 50 values comprised between 4.3 and 5.9 µg/ ml. These results were remarkably different from those reported by Yagi et al (2016) who found that the antiproliferative activity of C. schoenanthus aerial parts against these cell lines ranged between C. proximus 4.3 ± 0.5 4.4 ± 0.5 5.8 ± 0.8 >100 C. nervatus 4.4 ± 0.9 4.3 ± 0.5 5.9 ± 0.9 >100 Note: Results were obtained from the quadruplicate determination of two independent experiments (n = 8 using increasing concentrations (ranged from 0.5 to 400.0 μg/ml) of each essential oil.…”
Section: Antiproliferative Activitycontrasting
confidence: 98%
See 1 more Smart Citation
“…Although both oils showed different chemical profiles they exhibited high and comparable antiproliferative activity against the three tested cancer cell lines with IC 50 values comprised between 4.3 and 5.9 µg/ ml. These results were remarkably different from those reported by Yagi et al (2016) who found that the antiproliferative activity of C. schoenanthus aerial parts against these cell lines ranged between C. proximus 4.3 ± 0.5 4.4 ± 0.5 5.8 ± 0.8 >100 C. nervatus 4.4 ± 0.9 4.3 ± 0.5 5.9 ± 0.9 >100 Note: Results were obtained from the quadruplicate determination of two independent experiments (n = 8 using increasing concentrations (ranged from 0.5 to 400.0 μg/ml) of each essential oil.…”
Section: Antiproliferative Activitycontrasting
confidence: 98%
“…antiproliferative activity could be attributed to the composition and concentrations of essential oils which are mainly influenced by several factors including plant parts, stage of vegetative cycle, seasonal variation, geographical source, climatic and soil conditions, (Callan, Johnson, Westcott, & Welty, 2007). In fact, in this study, oil was extracted from a sample of C. schoenanthus inflorescences harvested from North Sudan, while that studied by (Yagi et al, 2016) was obtained from C. schoenanthus leafy stems growing in Western Sudan.…”
Section: Antiproliferative Activitymentioning
confidence: 95%
“…Antioxidant activity studies for the essential oil from three species of Cymbopogon , Cymbopogon citratus , Cymbopogon giganteus , and Cymbopogon proximus , by the DPPH free radical scavenging method, revealed a low potential when compared with the commercially used antioxidants t butylhydroxytoluene (BHT) and δtocopherol . The essential oil of Cymbopogon schoenanthus was also inactive for antioxidant potential . In an other study, Cymbopogon olivieri essential oil exhibited weak radical‐scavenging activity, reducing the DPPH radical formation ( IC 50 = 35 mg mL −1 ) in a dose‐dependent manner, with an efficacy lower than that of BHT .…”
Section: Resultsmentioning
confidence: 94%
“…Muitas espécies desse gênero produzem óleos essenciais e compostos bioativos que são valorizados por suas características aromáticas e terapêuticas, e que apresentam propriedades farmacológicas já comprovadas cientificamente, como anti-inflamatória, anticancerígena, antioxidante, antimicótica, antibacteriana e antiviral, o que as torna fontes promissoras de substâncias bioativas utilizadas para o tratamento de inúmeras doenças, bem como para a formulação de fármacos, coadjuvantes e inseticidas (ALMEIDA et al, 2013;RAMOS et al, 2013;CARVALHO et al, 2016;CORDEIRO et al, 2016;YAGI et al, 2016).…”
Section: Introductionunclassified